In vivo FRET imaging revealed a regulatory role of RanGTP in kinetochore-microtubule attachments via Aurora B kinase - Lee, Yoke Peng (2013)
Under the fluctuating circumstances provided by the innate dynamics of microtubules and opposing tensions resulted from microtubule-associated motors, it is vital to ensure stable kinetochore-microtubule attachments for accurate segregation. However, a comprehensive understanding of how this regulation is mechanistically achieved remains elusive. Using our newly designed live cell FRET time-lapse imaging, we found that post-metaphase RanGTP is crucial in the maintenance of stable kinetochore-microtubule attachments by regulating Aurora B kinase via the NES-bearing Mst1. More importantly, our study demonstrates that by ensuring stable alignment of metaphase chromosomes prior to segregation, RanGTP is indispensible in governing the genomic integrity and the fidelity of cell cycle progression. Our findings suggest an additional role of RanGTP beyond its known function in mitotic spindle assembly during the prometaphase-metaphase transition.